COMPARATIVE EFFECTIVENESS OF COPROOVOSCOPIC DIAGNOSTICS METHODS OF SHEEP DIGESTIVE TRACT NEMATODOSES - Melnychuk, V. V.; Yuskiv, I. D. (Scientific Progress & Innovations, 2019)
Diagnostic studies are an important component in a complex of measures aimed at achieving epizootic safety concerning parasitic animal diseases. At present, a large number of diagnostic methods and ways have been developed in the world, and they are divided into post-mortem and life-time. In their turn, the latter are divided into qualitative and quantitative. It should be noted that quantitative methods of diagnosing animal invasion diseases enable to assess objectively the level of the organism parazitation by a specific causal agent. Therefore, the development of effective and ergonomic methods of quantitative coproovoscopic diagnostics remains an urgent issue. In connection with the above mentioned the objective of the conducted research was to determine the effectiveness of well-known and improved methods of coproovoscopic diagnostics of sheep digestive tract nematodoses. The work was carried out in the Laboratory of the Department of Parasitology and Veterinary-Sanitary Expert Examination of Poltava State Agrarian Academy. Experimentally it was established that the improved method of quantitative coproovoscopic diagnostics of sheep digestive tract nematodoses turned out to be more effective, than the prototype method, as to the number of positive samples by 14.3 % and the number of found nematode eggs in the tested sample – by 18.5 %. High indices of diagnostic effectiveness were confirmed during production tests when comparing the improved method with the methods of analogues and prototype (Stoll, 1959; Trach, 1992; Liashenko et al., 2012; Taylor et al., 2015). According to the number of positive samples, the method was more effective by 8.0–44.0; concerning the minimal and maximal indices of the number of found nematode eggs in 1g of faeces the improved method was correspondingly by 14.3–80.9 % and 4.4–90.5 % more effective. According to the average number of nematode eggs in the sample as compared with the analogous methods: of Liashenko et al. the effectiveness was by 86.9 % higher, of Trach – by 37.9 %, and of Stoll – by 27.7 % higher, and by the prototype method – by 5.9 %. Analyzing the process of microscopy of the preparations made by different methods, it was found that the samples made in an improved way were the most convenient for the study. In the microscopic field, the smallest amount of foreign residues and air bubbles was detected, which did not interfere with the process of microscopy and the calculation of invasive elements.